Resistant Hinduism: Sanskrit Sources on Anti-Christian Apologetics in Early Nineteenth-Century India - Podgorski, Frank R (Journal of Dharma, 1983)
Richard Fox Young Resistant Hinduism: Sanskrit Sources on Anti-Christian Apologetics in Early Nineteenth-Century India Vienna: De Nobili Research Library, 1981, 200 pp. Gld. 50.